(untitled) (Acta Polytechnica CTU Proceedings, 2017)
This paper discusses issues of growth of a thin oxide layer formed on the surface of titanium alloys. The oxide layer on the surface introduces a corrosion resistance and a bio-compatibility, both of which are required for medical applications. The oxide layer is a result of a spontaneous passivation, but for the practical applications it is necessary to control the growth of oxides. In present work, the oxide layer was formed on the CP Ti grade 2, Ti39Nb alloy and CP Ti grade 2 with Ti39Nb PVD coating of two different thicknesses by a thermal oxidation at 600 °C for 8 hours. After the oxidation process the oxide layer was observed by SEM.